2017
DOI: 10.1007/s12664-017-0803-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequential testing with different tissue transglutaminase antibodies, a new approach for diagnosis of celiac disease

Abstract: Sequential testing for anti-tTG using first a highly sensitive assay followed by a very specific assay is a new strategy for screening for CeD in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…It was believed that ELISA tests would be more easily accessible and fairly priced in the setting where the research was conducted and will be used in future clinical screenings. Our findings indicate that ELISA identified more positive results than RBA, which is in line with our previous studies demonstrating that ELISA had lower specificity but equivalent sensitivity to RBA ( 22 , 23 , 41 ). In addition, we found that HLA-DQ2 and/or DQ8 were presented in all CDA-positive children, with an exception of one child whose sequencing phase failed during the genetic analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was believed that ELISA tests would be more easily accessible and fairly priced in the setting where the research was conducted and will be used in future clinical screenings. Our findings indicate that ELISA identified more positive results than RBA, which is in line with our previous studies demonstrating that ELISA had lower specificity but equivalent sensitivity to RBA ( 22 , 23 , 41 ). In addition, we found that HLA-DQ2 and/or DQ8 were presented in all CDA-positive children, with an exception of one child whose sequencing phase failed during the genetic analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Baseline screening for CDA started at 2 years of age by measuring IgA-neoepitopes against tTGA as previously described (AESKULISA tTg-A New generation, AESKU DIAGNOSTICS GmbH & Co. KG Mikroforum Ring 2 55234 Wendelsheim, Germany) ( 22 24 ). Antibody levels were expressed in U/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, due to false positive results that are relatively common due to the high specificity of reverse immunofluorescence for the detection of EMA antibodies, the EMA test for patients with suspected celiac disease is often performed as a confirmatory test before biopsy in individuals who have a TTG-positive test. 17 The sensitivity and specificity of the TTG test in the diagnosis of celiac disease when the EMA test is also positive is about 100%. 18 Reverse immunofluorescence detection causes problems for EMA antibody observation due to different levels of observer skill, interference with anti-nuclear or anti-smooth muscle antibodies, as well as different standards from laboratory to laboratory in interpreting EMA testing.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Indian Journal of Gastroenterology, Venugopal et al [1] propose a two-tier auto-antibody testing approach, as a screening strategy for celiac disease. Making use of two sequential tests with opposing sensitivity and specificity is a new and interesting approach which could benefit patient care.…”
mentioning
confidence: 99%
“…This is followed by testing the resulting positive samples with a highly specific but less sensitive test [1]. This resulted in two transglutaminase IgA antibody (TGA) positive individuals (0.1%) within a group of 1917 healthy adults from three semi-urban areas in South India.…”
mentioning
confidence: 99%